2021
DOI: 10.1155/2021/4977620
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Prediction Based on Adaptive BP Neural Network

Abstract: This paper uses adaptive BP neural networks to conduct an in-depth examination of eye movements during reading and to predict reading effects. An important component for the implementation of visual tracking systems is the correct detection of eye movement using the actual data or real-world datasets. We propose the identification of three typical types of eye movements, namely, gaze, leap, and smooth navigation, using an adaptive BP neural network-based recognition algorithm for eye movement. This study asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…(4) e input activation value s k j and the response output value z k j of each neuron in the hidden layer were calculated. Input activation value of neurons in hidden layer [23] is as follows:…”
Section: Algorithm and Steps Of Bp Model For Enterprise Comprehensive...mentioning
confidence: 99%
“…(4) e input activation value s k j and the response output value z k j of each neuron in the hidden layer were calculated. Input activation value of neurons in hidden layer [23] is as follows:…”
Section: Algorithm and Steps Of Bp Model For Enterprise Comprehensive...mentioning
confidence: 99%
“…In many cases, there are many factors affecting the results of the process, and it is necessary to analyze which indicators are more relevant or the correlation ranking of these factors, and the response results can be obtained by Grey correlation analysis. In this paper, GRA was used to determine the degree of correlation of multiple kinematic data for kinetic vGRF.Teng used GRA to optimize the construction of convolutional neural network system and the evaluation of drugs [18].Kong et al constructed a GRA-ANN to predict the effect of aggregates on the permeability of concrete [19]. Currently, GRA is more often used in engineering research, so it is hoped that this paper will open up GRA for research in sports disciplines.…”
Section: Introduction:mentioning
confidence: 99%
“…e development of big data and information technology [11][12][13][14] provides a reliable supporting tool for this research. Many studies have found that some eye movement parameters [15][16][17], such as fixation duration, fixation duration percentage, fixation frequency, regression frequency, and average pupil diameter, provided critical evidence to explore the psychological process of students. Tai [18] compared the eye movement differences in problem-solving behaviors of participants with different professional backgrounds in scientific evaluation and found that the eye movement differences were related to the participant's professional level on a specific topic.…”
Section: Introductionmentioning
confidence: 99%